HUBUNGAN PENGETAHUAN DENGAN SIKAP IBU DALAM PEMBERIAN IMUNISASI DASAR PADA BAYI USIA 0-12 BULAN DI POSYANDU TIRTOMULYO DESA JOHO KECAMATAN WATES KABUPATEN KEDIRI - Puspitasari, Betristasia; Darmayanti, Rofik (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2023)
Background: Immunization is a program that babies need for the present and future to avoid certain diseases. Efforts to reduce morbidity and mortality rates in children include immunization. The purpose of this study was to determine the relationship between knowledge and maternal attitudes in providing basic immunization to infants aged 0-12 months. Methods: The research method used correlation with the cross sectional approach. The population of this study was all mothers who had babies aged 0-12 months at Posyandu Tirtomulyo, Joho Village, Wates District, Kediri Regency as many as 37 respondents. The sample taken in this study was 32 respondents. Sampling technique with accidental sampling. Data collection using questionnaires, data processing, editing, coding, scoring and tabulating. Data analysis using Chi-Square. Result: The results of the study from 32 respondents, most of the respondents were well knowledgeable as many as 14 respondents (43.8%), knowledgeable enough as many as 10 respondents (31.2%) and less knowledgeable as many as 8 respondents (25%), while for maternal attitudes in providing basic immunization with positive attitude categories as many as 23 respondents (71.9%) and negative attitudes as many as 9 respondents (28.1%). From the Chi-Square analyst test, it shows p value = 0.000 (p value < 0.05), then H1 is accepted, H0 is rejected, meaning that there is a relationship between knowledge and maternal attitudes in providing basic immunization to infants aged 0-12 months. Discussion: It can be concluded that there is a relationship between knowledge and maternal attitudes in providing basic immunization to infants aged 0-12 months. To further increase the knowledge of mothers of infants who are still lacking about the importance of basic immunization, it is recommended that the government through health workers provide health education to mothers to be positive about basic immunization. So it is expected to achieve complete basic immunization coverage for each child.